Gambaran Self Care Behaviour Pada Pasien Hipertensi di Puskesmas Wilayah Kota Denpasar - Meril Valentine Manangkot; I Made Suindrayasa (Coping: Community of Publishing in Nursing, 2020)
Hypertension is a chronic disease. Hypertension can be divided into two, namely primary hypertension and secondary hypertension. The high incidence of hypertension currently requires commitment in the management of sustainable hypertension. One of them is developing adequate self care behaviour. This study aimed to identify the description of self care behaviour in hypertension patients in Denpasar. Respondents were 115 hypertension patients in 3 community health centers in Denpasar. Data collected using questionnaire with consecutive sampling technique. Univariate data analysis is described with frequency distribution and central tendency. The results showed that the average score of self care behaviour was 20.30, with the highest score was 28, and the lowest score was 10. Keywords: hypertension, complication, self care behaviour